2004
DOI: 10.1111/j.1527-5299.2004.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History, Epidemiology, and Prognosis of Heart Failure in African Americans

Abstract: Heart failure is more common in African Americans and appears to be of worse severity. At the time of diagnosis, left ventricular function is more severely impaired and the clinical class is more advanced. The strongest risk factor for heart failure in African Americans appears to be hypertension, which is both more prevalent and more pathologic in African Americans. It is likely that heart failure represents an important end organ effect of hypertension. When affected by heart failure, African Americans exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…It is therefore possible that residual confounding could in part account for our findings. Lastly, healthy controls in our sample were predominantly white, whereas nearly half of participants with MS were black, an important point since LV hypertrophy, 28 and diastolic dysfunction, are more prevalent among blacks. Our sample size was not powered to examine racial differences, however, the primary study results were not materially different in sensitivity analyses including only whites.…”
Section: Discussionmentioning
confidence: 93%
“…It is therefore possible that residual confounding could in part account for our findings. Lastly, healthy controls in our sample were predominantly white, whereas nearly half of participants with MS were black, an important point since LV hypertrophy, 28 and diastolic dysfunction, are more prevalent among blacks. Our sample size was not powered to examine racial differences, however, the primary study results were not materially different in sensitivity analyses including only whites.…”
Section: Discussionmentioning
confidence: 93%
“…5 Potential mechanisms for worse outcomes in black patients with HF include the more malignant pathophysiology of hypertension in blacks, the higher prevalence and severity of left ventricular hypertrophy, an impaired vasodilatory response, and genetic polymorphisms. 3,4,27 Additional unrecognized differences in the pathophysiology of HF in blacks remain an alternative explanation. Disparities in health care access, along with a greater burden of socioeconomic stressors, may be associated with increased adverse events in black patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Elderly black Medicare patients were recently shown to have increased 30-day readmission rates for HF compared with whites. 5 However, several studies during the 1990s in the Veterans Affairs health care system 6,7 and in Medicare patients 8 demonstrated better survival in black patients with HF compared with white patients.…”
mentioning
confidence: 99%
“…11 Thus, elevated pulmonary artery diastolic pressure (a surrogate for LV filling pressure) may, in part, explain why African Americans with HF have a worse prognosis compared with patients of other racial groups. 7,20,21 The Studies of Left Ventricular Dysfunction were among the first to suggest differential HF outcomes as a function of race. 22 A post hoc analysis of the primary trial results demonstrated that mortality from HF was higher in African Americans than in Caucasians, with a 1.8-fold increase for African American men and a striking 2.4-fold increase for African American women.…”
Section: Discussionmentioning
confidence: 99%